Clear cell ovarian cancers with microsatellite instability: A unique subset of ovarian cancers with increased tumor-infiltrating lymphocytes and PD-1/PD-L1 expression. (1st February 2017) - Howitt, Brooke E.; Strickland, Kyle C.; Sholl, Lynette M.; Rodig, Scott; Ritterhouse, Lauren L.; Chowdhury, Dipanjan; D'Andrea, Alan D.; Matulonis, Ursula A.; Konstantinopoulos, Panagiotis A.
ABSTRACT: Clear cell ovarian carcinoma (CCOC) represents a distinct histologic subtype of ovarian cancer associated with significantly worse prognosis across all stages and no effective therapeutic options. Here, we report a rare but clinically important cohort of CCOCs with microsatellite instability (MSI) (MSI-CCOCs), which are highly immunogenic and may thus be very responsive to immune checkpoint blockade. CCOCs with MSI exhibit a significantly higher number of CD8 + TILs, higher CD8 + /CD4 + ratio, and higher PD-1 + TILs compared with microsatellite stable (MSS) CCOCs and compared with high grade serous ovarian cancers, which are the most common histologic subtype of ovarian cancer. Of note, PD-L1 expression in tumor cells or immune cells was noted in all cases of CCOCs with MSI. These observations open an alternative therapeutic avenue for a fraction of patients with CCOC and argue for the routine testing of CCOCs for MSI, a test that is not currently routinely performed.